Obesity in Maine: A Policy Approach - Mills, Dora (Maine Policy Review, 2004)
Compared to earlier generations, Americans are eating more, making poorer nutritional choices, and are less physically active. The result is an “obesity epidemic” facing Maine and the nation. Dora Anne Mills, director of Maine’s Bureau of Health, summarizes the extent, impact, and causes of obesity, and presents policy solutions suggested in public health and medical literature. Because the factors behind the obesity epidemic are so interwoven in the fabric of society, policymakers, businesses and individuals must consider a variety of solutions on the personal, local, state and national levels. Mills warns if we do not act soon and systematically, “our youth may be the first generation to not live as long as their parents’ generation.”